Psychiatric diagnosis and chronic fatigue syndrome: Controversies and conflicts - Sharpe, M (2005)
There is controversy about the making of psychiatric diagnoses in patients who have a diagnosis of chronic fatigue syndrome. The scientific controversies concern the purposes of diagnosis for the patient as well as for the doctor, the separation of diagnoses into medical and psychiatric and the intrinsically overlapping nature of symptom defined syndromes. The conflict arises from the practical and moral meaning of diagnoses, especially psychiatric diagnoses. At present the best clinical solution may to be make combined diagnoses such as CFS/depression. However, this apparently small issue should encourage us to ask the bigger question about the nature and purpose of diagnosis. Conflict of interest. None. © Shadowfax Publishing and Taylor and Francis Group Ltd.